Peran Komunikasi dalam Membangun Hubungan Antar Individu dan Dinamika Tim terhadap Peningkatan Kinerja Karyawan di Kafe Otsukohi - Adinda Dwi Mulyani; Sahrul Sodikin; Suheti Suheti; Annisa Putria Rachmawati; April Laksana (Federalisme: Jurnal Kajian Hukum dan Ilmu Komunikasi, 2024)
This study shows that team collaboration dynamics greatly affect work quality and goal achievement. These dynamics include various elements, including communication, coordination, interdependence, and trust among team members. The methodology of this study aims to provide detailed insights into team collaboration dynamics and work efficiency, with a focus on organizational success in achieving organizational goals. The interpersonal communication patterns of managers that were found and had a significant impact on Caffe Otsukohi team performance were democratic communication patterns and laissez-faire communication patterns. Supporting factors for interpersonal communication between managers and Caffe Otsukohi employees include transformational leadership, a positive work environment, effective communication channels, and shared goals.